2014
DOI: 10.1149/2.0871412jes
|View full text |Cite
|
Sign up to set email alerts
|

Post-Polymerization Electrochemical Functionalization of a Conducting Polymer: Diazonium Salt Electroreduction at Polypyrrole Electrodes

Abstract: In this paper we report the functionalization of conductive polypyrrole (PPY) films via electrochemical reduction of the aryl diazonium salts in a manner that is similar to the one employed for other conductive surfaces. To understand the general trends of the grafting behavior of diazonium salts and to establish the optimal conditions for the covalent functionalization of the PPY films, we have compared the grafting behavior of four p-substituted phenyldiazonium salts: p-nitrophenyl diazonium tetrafluoroborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…As reported in our previous study concerning several parasubstituted arenediazonium salts [10], also in the case of NABDBF 4 À the reduction at the polypyrrole electrode occurs more easily (E p approx. +0.1 V) than at the other electrodes (E p approx.…”
Section: Electrochemical Reduction Of 4-[(4 0 -Nitrophenyl)azo] Benzesupporting
confidence: 70%
See 2 more Smart Citations
“…As reported in our previous study concerning several parasubstituted arenediazonium salts [10], also in the case of NABDBF 4 À the reduction at the polypyrrole electrode occurs more easily (E p approx. +0.1 V) than at the other electrodes (E p approx.…”
Section: Electrochemical Reduction Of 4-[(4 0 -Nitrophenyl)azo] Benzesupporting
confidence: 70%
“…This represents a confirmation of our previous results discussed in ref. [10] which concern the electrochemical functionalization of polypyrrole with para-substituted phenyl groups via diazonium chemistry.…”
Section: Third-order Nonlinear Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible atoms for this new compound in the working gas air are nitrogen and oxygen. According to various studies investigating different CNO bonds, we conclude that the new N1s peak can be attributed to either NO3 or NO 2 …”
Section: Resultsmentioning
confidence: 75%
“…However, several studies revealed that the substituent in the para - position has a strong influence on the proneness for spontaneous grafting, and salts with electron-withdrawing substituents are able to spontaneously graft even onto less-reducing substrates, such as carbon [ 132 , 161 ]. Among the different functionalization methods, the electrochemical reduction of aryldiazonium salts is the most popular since it allows a higher degree of derivatization control, and the process is straightforward and expeditious [ 36 , 131 , 161 , 162 , 163 , 164 , 165 ]. The potential of the characteristic diazonium electroreduction peak evidenced in cyclic voltammograms (CVs) is useful for assessing diazonium reactivity, as it is directly influenced by the nature of substituents on the aromatic ring [ 132 , 141 , 161 , 163 , 164 , 165 , 166 , 167 ].…”
Section: The Role Of Diazonium Electrochemistry For Aptasensors Developmentmentioning
confidence: 99%